Speech Specialists’ Perspective on Family Interventions that Reduce Some Communication Disorders Among Students with Intellectual Disabilities in Makkah Al-Mukarramah City - Bakhsh, Raghdah Imtiaz Hussain; Alharbi, Ghadah Ghazi (Journal of Educational and Psychological Sciences, 2022)
The present study aims to identify the salient family interventions that potentially reduce some of the communication disorders among students with Intellectual disabilities from the perspective of Speech Therapists in Mecca, Saudi Arabia. A questionnaire consisting of three sections and 25 items was developed to achieve the study objectives. The questionnaire was developed based on educational literature and consists of three sections namely, family interventions related to diagnosis and evaluation, family interventions related to designing and implementing individual educational plan and family interventions related to assessing individual educational plan and its implementation. The results of the study show that all sections of the questionnaire (i.e. family interventions related to evaluating educational plan and its implementation, family interventions related to evaluation and diagnosis, family interventions related to developing and implementing individual educational plan) respectively. The results also indicates that there are no statistically significant differences among work experience, gender and educational qualification of Speech Therapists in Mecca, Saudi Arabia. Based on these results, the study makes the following recommendations: giving attention to the perspective of Speech therapists on family interventions that potentially reduce some of the communication disorders among students with intellectual disabilities and engage families of these students; conducting training courses for families of these students on how to engage families in the programs provided to their children; building community partnership that can achieve 2030 vision of Kingdom of Saudi Arabia.